2015
DOI: 10.1111/1346-8138.13079
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in bullous pemphigoid: A controversial association

Abstract: Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disorder that has been reported to be associated with malignancies. Some authors described several cases of pemphigoid associated with malignancies (PAM); however, the evidence of this correlation still remains controversial. Several theories have been postulated to explain the relationship between malignant neoplasms and BP; the main theory suggests that antibodies directed against tumor-specific antigens of malignant cells may cross-react with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 52 publications
1
39
0
12
Order By: Relevance
“…In the current case, the chronology and the lack of BP‐inducing drugs in the medication history suggested an unambiguous clinical link between PRP and BP. Moreover, as both conditions may be associated with malignancies, we excluded any underlying neoplasm and, given that BP may rarely be complicated by erythroderma prior to or following blister formation, we also excluded erythrodermic BP by means of histopathology, which showed findings typical of PRP.…”
mentioning
confidence: 99%
“…In the current case, the chronology and the lack of BP‐inducing drugs in the medication history suggested an unambiguous clinical link between PRP and BP. Moreover, as both conditions may be associated with malignancies, we excluded any underlying neoplasm and, given that BP may rarely be complicated by erythroderma prior to or following blister formation, we also excluded erythrodermic BP by means of histopathology, which showed findings typical of PRP.…”
mentioning
confidence: 99%
“…The results of an examination of 1113 patients with BP in Japan revealed the presence of malignant tumor in 64 (5.8%) patients . In addition, it has been reported in Italy (10.9%), Taiwan (15.1%) and the UK (17.9%) that the malignant tumor complication rates are higher compared with the general population, but evidence of a causal relationship has not been clearly demonstrated. A study from Singapore reported that the malignant tumor complication rate was 13.4%, but they concluded that there was no significant increase in the malignant complication rate in patients with BP compared with that of the general population .…”
Section: Overview Of Pemphigoid Diseasesmentioning
confidence: 97%
“…Lastly, the PD may not respond to the treatment of malignancy, such as paraneoplastic pemphigus (PNP). 1 BP is characterized by formation of autoantibodies against BP antigen 1 (BPAg1) and 2 (BPAg2). Data pertaining to pemphigoid associated with malignancy (PAM) is heterogeneous.…”
mentioning
confidence: 99%
“…Some studies report an enhanced risk of malignancies (around 5.8-19%) in BP compared to general population, whereas some report that few malignancies (laryngeal cancer, renal cell carcinoma and lymphoid malignancies) herald an increased risk of developing BP. [1][2][3] Cross-reaction between tumour and hemidesmosome antigens, tumour-mediated basement membrane damage and subsequent antibody response and a common predisposing genetic background (HLA-B13) are some of the theories proposed for the development of PAM. Unlike PNP, PAM is essentially similar to classical BP, with slightly more mucosal involvement.…”
mentioning
confidence: 99%
See 1 more Smart Citation